Cardiomyopathy Induced by Artificial Cardiac Pacing: To Whom, When, Why, and How? Insights on Heart Failure Development - Ferrari, Andres Di Leoni; Oliveira, Eduardo Bartholomay; Tagliari, Ana Paula; Kochi, Adriano Nunes; Beuren, Thaís Mariel Andara; Cabral, Gustavo Chiari; Ferreira, Flávio Vinicius Costa; Danzmann, Luiz Cláudio (Revista brasileira de cirurgia cardiovascular, 2023)
Coordinated and harmonic (synchronous) ventricular electrical activation is essential for better left ventricular systolic function. Intraventricular conduction abnormalities, such as left bundle branch block due to artificial cardiac pacing, lead to electromechanical "dyssynchronopathy" with deleterious structural and clinical consequences. The aim of this review was to describe and improve the understanding of all the processes connecting the several mechanisms involved in the development of artificially induced ventricular dyssynchrony by cardiac pacing, most known as pacing-induced cardiomyopathy (PiCM). The chronic effect of abnormal impulse conduction and nonphysiological ectopic activation by artificial cardiac pacing is suspected to affect metabolism and myocardial perfusion, triggering regional differences in the activation/contraction processes that cause electrical and structural remodeling due to damage, inflammation, and fibrosis of the cardiac tissue. The effect of artificial cardiac pacing on ventricular function and structure can be multifactorial, and biological factors underlying PiCM could affect the time and probability of developing the condition. PiCM has not been included in the traditional classification of cardiomyopathies, which can hinder detection. This article reviews the available evidence for pacing-induced cardiovascular disease, the current understanding of its pathophysiology, and reinforces the adverse effects of right ventricular pacing, especially right ventricular pacing burden (commonly measured in percentage) and its repercussion on ventricular contraction (reflected by the impact on left ventricular systolic function). These effects might be the main defining criteria and determining mechanisms of the pathophysiology and the clinical repercussion seen on patients.